2017
DOI: 10.1073/pnas.1612098114
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium -delivered virulence protein VirE2 is trafficked inside host cells via a myosin XI-K–powered ER/actin network

Abstract: Agrobacterium tumefaciens causes crown gall tumors on various plants by delivering transferred DNA (T-DNA) and virulence proteins into host plant cells. Under laboratory conditions, the bacterium is widely used as a vector to genetically modify a wide range of organisms, including plants, yeasts, fungi, and algae. Various studies suggest that T-DNA is protected inside host cells by VirE2, one of the virulence proteins. However, it is not clear how Agrobacterium-delivered factors are trafficked through the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 53 publications
4
39
0
Order By: Relevance
“…Chemical disruptions of microtubule networks and dynein motors blocked VirE2 complex movement, suggesting the possible involvement of microtubules in A. tumefaciens T-complex nuclear targeting (Salman et al, 2005;Tzfira, 2006). However, cytoskeleton inhibitor treatment together with real time VirE2 trafficking imaging experiments in N. benthamiana demonstrated that cytoplasmic movement of VirE2 does not require microtubules but does rely on actin powered by myosin (Yang et al, 2017). The involvement of actin in VirE2 trafficking is also supported by the findings that Arabidopsis mutant plants impaired in actin genes (ACT2, At3g18780 and ACT7, At5g09810) expressed in the roots were resistant to stable and transient transformation, suggesting the involvement of the actin cytoskeleton in Agrobacterium-mediated transformation (Zhu et al, 2003b).…”
Section: Cytoplasmic Trafficking and Nuclear Import Of T-dna And Effementioning
confidence: 98%
See 1 more Smart Citation
“…Chemical disruptions of microtubule networks and dynein motors blocked VirE2 complex movement, suggesting the possible involvement of microtubules in A. tumefaciens T-complex nuclear targeting (Salman et al, 2005;Tzfira, 2006). However, cytoskeleton inhibitor treatment together with real time VirE2 trafficking imaging experiments in N. benthamiana demonstrated that cytoplasmic movement of VirE2 does not require microtubules but does rely on actin powered by myosin (Yang et al, 2017). The involvement of actin in VirE2 trafficking is also supported by the findings that Arabidopsis mutant plants impaired in actin genes (ACT2, At3g18780 and ACT7, At5g09810) expressed in the roots were resistant to stable and transient transformation, suggesting the involvement of the actin cytoskeleton in Agrobacterium-mediated transformation (Zhu et al, 2003b).…”
Section: Cytoplasmic Trafficking and Nuclear Import Of T-dna And Effementioning
confidence: 98%
“…Because translocated VirE2 forms the filamentous structure in the absence of T-DNA, the associations and assistance of host plant cell proteins may be required for VirE2 movement (Li et al, 2014b;Sakalis et al, 2014). Indeed, using split-GFP technology to visualize VirE2 movement in agroinfiltrated N. benthamiana leaf epidermal cells, recent studies showed that VirE2 is transported into plant cells via clathrin-mediated endocytosis and trafficked via an ER/actin network that is powered by myosin XI-K (Yang et al, 2017).…”
Section: Cytoplasmic Trafficking and Nuclear Import Of T-dna And Effementioning
confidence: 99%
“…Despite the importance of bacterial effectors in the modulation of host-microbe interactions, direct TTSS effector delivery has not been visualized in whole organisms. Recently, delivery of the virulence protein VirE2 by Agrobacterium tumefaciens through the type IV secretion system was successfully visualized using the GFP strand system in yeast, Arabidopsis, and tobacco (Nicotiana tabacum; Li et al, 2014;Li and Pan, 2017;Yang et al, 2017). The type IV secretion system is responsible for delivery and uptake of proteins and DNA, with a conduit diameter of ;18.5 nm (Wallden et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the cell-tocell spread of Tobacco mosaic virus and Grapevine fanleaf virus in N. benthamiana leaf epidermis could be reduced by overexpressing Myo11B and Myo11E tail constructs (Amari et al, 2011(Amari et al, , 2014, again confirming a role of these motors in the transport of viruses. Interestingly, a similar myosin-dependent movement was detected for the VirE2 protein of Agrobacterium tumefaciens that is injected into plant cells together with the T-DNA (Yang et al, 2017). At this point, it is not clear whether the viruses or VirE2 interact directly with myosin motors or whether they are moved passively together with endogenous organelles, since these experimental interventions also reduced organelle motility.…”
Section: Plant-pathogen Interactions Reveal New Functions Of Myosin Mmentioning
confidence: 94%